2017
DOI: 10.3389/fnins.2017.00169
|View full text |Cite
|
Sign up to set email alerts
|

Using Cochlear Microphonic Potentials to Localize Peripheral Hearing Loss

Abstract: The cochlear microphonic (CM) is created primarily by the receptor currents of outer hair cells (OHCs) and may therefore be useful for identifying cochlear regions with impaired OHCs. However, the CM measured across the frequency range with round-window or ear-canal electrodes lacks place-specificity as it is dominated by cellular sources located most proximal to the recording site (e.g., at the cochlear base). To overcome this limitation, we extract the “residual” CM (rCM), defined as the complex difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…To extract more precise frequency specific information about sensory hearing loss from the eCochG, it is better to consider not the responses to the stimulus tones directly, but to use them to evoke a nonlinear cochlear response that is location specific, related to the stimulus CL. This strategy was demonstrated 13 by exploiting the phenomenon of cochlear two-tone suppression to identify and localize cochlear deficiencies from the RW-eCochG. Here we used another nonlinear, cochlear phenomenon, the generation of DPs (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To extract more precise frequency specific information about sensory hearing loss from the eCochG, it is better to consider not the responses to the stimulus tones directly, but to use them to evoke a nonlinear cochlear response that is location specific, related to the stimulus CL. This strategy was demonstrated 13 by exploiting the phenomenon of cochlear two-tone suppression to identify and localize cochlear deficiencies from the RW-eCochG. Here we used another nonlinear, cochlear phenomenon, the generation of DPs (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…However, location-specific information is available in the CM, and it can be extracted when the evaluated responses rely on CL-specific response properties of the cochlea. For example, Charaziak et al 13 demonstrated that CM responses can be used to detect and localize sensory hearing loss by exploiting the local, cochlear phenomenon of two-tone suppression.…”
Section: Introductionmentioning
confidence: 99%
“…The CM is an indication of electrical current flow through OHCs and has shown potential to be developed into a diagnostic measure (Withnell, 2001;Cheatham et al, 2011). Research by Chertoff and colleagues (2012Chertoff and colleagues ( , 2014Chertoff and colleagues ( , 2015, Kamerer et al (2016), and Charaziak et al (2017) has provided evidence in rodent models that CM can be used to assess OHCs in a locationspecific manner.…”
Section: Introductionmentioning
confidence: 99%
“…This could confound attempts to diagnose the health of OHCs in the apex (Dallos, 1969;Patuzzi et al, 1989). Several studies have developed methods of resolving this issue, using high-pass noise to suppress responses from OHCs outside a targeted region of the cochlear partition (Chertoff et al, 2012b(Chertoff et al, , 2014Kamerer et al, 2016;Charaziak et al, 2017). A third inherent issue with RW recording is the addition of AN activity in the response (Patuzzi et al, 1989;Henry, 1995;He et al, 2012;Lichtenhan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%